In silico evidence of monkeypox F14 as a ligand for the human TLR1/2 dimer - Chakraborty, Ankita; Das, Nabarun Chandra; Gupta, Parth Sarthi Sen; Panda, Saroj Kumar; Rana, Malay Kumar; Bonam, Srinivasa Reddy; Bayry, Jagadeesh; Mukherjee, Suprabhat (Frontiers in Immunology, 2025)
Recent emergence of zoonotic monkeypox virus (Mpox) in human has triggered the virologists to develop plausible preventive measures. Hitherto, our understanding on the mechanism of immunopathogenesis of Mpox infection is elusive. However, available experimental evidences suggest induction of inflammation as the main cause of pathogenesis. Toll-like receptors (TLRs) are critical in initiating and modulating the host immune response to pathogens. Inflammatory responses observed in various poxvirus infections have, in fact, been shown to be mediated through TLR activation. Therefore, by in silico approaches, this study seeks to identify the Mpox antigen(s) (MAg) that are most likely to interact with human cell-surface TLRs. The Mpox proteomics data available in UniProt database contain 174 protein sequences, among which 105 immunoreactive proteins were modeled for 3D structure and examined for comparative protein-protein interactions with the TLRs through molecular docking and molecular dynamics simulation. F14, an 8.28 kDa infective protein of Mpox, was found to exhibit strong binding affinity (ΔG=-12.5 Kcal mol-1) to TLR1/2 dimer to form a compact thermodynamically stable protein complex. Interestingly, a significant level of conformational change was also observed in both F14 and TLR6 while forming F14-TLR1/2 complex. Based on these data we propose F14 as a putative ligand of human TLR1/2 to initiate proinflammatory signaling in the Mpox-infected host.